2017
DOI: 10.1016/j.gexplo.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of factors affecting mercury emission from subtropical forest soil: A field controlled study in southwestern China

Abstract: Recent studies demonstrated that subtropical forest in China was considered as a large pool of atmospheric mercury and soils of forested watershed is a large reservoir of atmospherically deposited mercury. However, forest ecosystems not only act as sinks but also as sources of previously deposited mercury emitted back to the atmosphere. In this study a field controlled method was performed in Tieshanping National Forest Park (TNFP) to identify the effects of the most important parameters that controlled mercur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 45 publications
4
17
0
Order By: Relevance
“…4) and mineral layers are hence substantially lower than in the overlying litter horizons. Deeper soil layers showed lower mercury concentrations as compared to upper soil horizons which is also evident by our previous study in this area (Zhou et al, 2016), and mercury concentrations drop strongly from A to B horizon. Declining mercury concentrations with soil depth are commonly observed: Zhou et al (2013) reported declining mercury concentrations from top horizons to deep horizons in a broad-leaf primary forest in Southwestern China; soil concentrations decreased sharply with depth in mineral horizons in Jeffrey pines forest in USA (Obrist et al, 2009);and Liu et al (2003) reported decreasing mercury concentrations in the peat blog of Xiaoxing'an Mountain, northeastern China with highest mercury concentrations in the top horizons.…”
Section: Mercury Concentrations and Pools In Soils 331 Mercury Consupporting
confidence: 85%
See 1 more Smart Citation
“…4) and mineral layers are hence substantially lower than in the overlying litter horizons. Deeper soil layers showed lower mercury concentrations as compared to upper soil horizons which is also evident by our previous study in this area (Zhou et al, 2016), and mercury concentrations drop strongly from A to B horizon. Declining mercury concentrations with soil depth are commonly observed: Zhou et al (2013) reported declining mercury concentrations from top horizons to deep horizons in a broad-leaf primary forest in Southwestern China; soil concentrations decreased sharply with depth in mineral horizons in Jeffrey pines forest in USA (Obrist et al, 2009);and Liu et al (2003) reported decreasing mercury concentrations in the peat blog of Xiaoxing'an Mountain, northeastern China with highest mercury concentrations in the top horizons.…”
Section: Mercury Concentrations and Pools In Soils 331 Mercury Consupporting
confidence: 85%
“…Via atmospheric long-distance transport, large amounts of mercury deposited to the surrounding region of the city. Based on our previous studies here, the annual total input fluxes of mercury were 291.2 mg m À2 yr À1 ), which was several or even dozens of times higher than those in North America and Europe (Zhou et al, 2016). About over two-thirds of the deposited mercury was resident in the forest, which resulted in elevated mercury concentration in organic horizons (191 ± 65 ng g À1 ) and mercury pool (8.2 ± 2.6 mg m…”
Section: Study Areamentioning
confidence: 62%
“…Previous studies suggested that soil moisture contributed to TGM flux had optimum interval and should be under intermediate conditions, neither under fairly dry nor very wet (Gustin and Stamenkovic, 2005;Lin et al, 2010;Pannu et al, 2014;Obrist et al, 2014;Zhou et al, 2017b), which can elucidate the different correlations at different forest ecosystems. Fig.…”
Section: Export Of Soil-atmosphere Exchange Fluxesmentioning
confidence: 99%
“…The relationship is mainly attributed to photochemical reduction of soilbound Hg, which converts soil Hg 2+ to volatile Hg 0 (Amyot et al, 1994(Amyot et al, , 1997Carpi and Lindberg, 1997;Moore and Carpi, 2005;Xin et al, 2007;Zhou et al, 2017b). Photo-reduction is a major driver of Hg 0 generation and evasion from soils (Choi and Holsen, 2009;Engle et al, 2001;Zhou et al, 2015aZhou et al, , 2017b, although other abiotic and biotic processes also resulted in translation of Hg 2+ to Hg 0 production, including reduction by humic acids (Alberts et al, 1974;Allard and Arsenie, 1991) and iron oxides under anoxic conditions (Lin and Pehkonen, 1997) as well as reduction by microorganisms (Siciliano et al, 2002;Agnan et al, 2016) and/or microbial exudates (Poulain et al, 2007(Poulain et al, , 2004Fritsche et al, 2008). Additionally, other important correlation was identified with soil or air temperature, which is also significantly correlated to the Hg 0 production and observed with soil-atmosphere Hg flux in all the forests in China (n=30).…”
Section: Export Of Soil-atmosphere Exchange Fluxesmentioning
confidence: 99%
See 1 more Smart Citation